Leaching Studies of Braunite With Sulphuric Acid and Phenol-Reducer - PAZOKI, AMIR (Asian Journal of Chemistry, 2010)
In this paper, sampling was carried out on the manganese deposit at Benesbord, 65 kilometers northwest Sabzevar in Khorasan, as the representative of the province deposits (regarding mineralogy and genesis) and its mineral dressing operations were conducted. The main minerals constituting this ore include quartz, braunite (manganese silicate) and hematite in which the weight percentages of SiO2, Mn and Fe2O3 are 64.5, 14.0 and 8.5 %, respectively. Owing to its genesis, this ore has two structures. First, filling into vein lets which may be concentrated through (shaking table and jig) physical methods. The other one, being dispersed throughout the whole ore, has dimensions of about some microns. It may not be recovered and concentrated with the above-motioned physical methods, having a gangue grade of at least ca. 6 %. Thus, for the complete recovery of manganese in the ore, the leaching operations were performed using sulphuric acid and the phenol-reducer on the sample with dimensions of about 1 mm. However, the final findings suggested that the recovery of the leaching operations using sulphuric acid and the phenol-reducer, in different weight percentages and amounts, were not successful, reaching a maximum of ca. 13.5 %.